Training on the Use of Fruit Dryer Technology for Optimizing MSME Production of Marning Mesuji - Suaidah, Suaidah; Aldino, Ahmad Ari; Ningtyas, Kurnia Rimadhanti; Oktaviani, Lulud; Surahman, Ade; Sintaro, Sanriomi; Budiono, Andiswar Muhamad; Lestari, Yuni Tri (International Journal of Public Devotion, 2023)
Margo Jadi Village, Mesuji Timur District, Mesuji Regency, Lampung Province is one of the Micro, Small and Medium Enterprises (MSME) groups in the category of micro businesses engaged in selling marning corn. Marning corn is a snack that is consumed after going through a simple processing. MSME Corn marning Mesuji is managed by an industrial house consisting of several houses, namely Mr. Sahid, Mrs. Lina, Mr. Sumarnak Mrs. Maryati, Mrs. Mislah and Mrs. Sudarsih which were established in 2000. Every member of the MSME marning also cooperates with each other in all matters relating to marning production. Every MSME production of Mesuji marning corn can reach 100 kg per week to be sent out of town such as Jambi city. The production of marning is carried out with inadequate tools, to dry corn which is still conventionally boiled, that is, relying on sunlight. The team provided training on automatic fruit dryer technology which can dry wet corn quickly, not affected by the weather, the water content in boiled corn will be reduced to the maximum and make the drying process more awake and organized. With MSME partners dryers can dry marning corn more hygienic and protected from dust or dirt because corn is dried in a closed room